1989
DOI: 10.1111/j.1432-1033.1989.tb14631.x
|View full text |Cite
|
Sign up to set email alerts
|

Zonal distribution of fatty acid synthase in liver parenchyma of male and female rats

Abstract: 1. A sensitive radiochemical assay was established to determine the activity of fatty acid synthase in microdissected liver tissue of less than 1 pg dry mass.2. In female rats, the enzyme activity in perivenous tissue was twice that in periportal liver tissue while it was homogeneously distributed in livers of male animals. The overall activity was higher in female than in male animals.3. The absolute activity, as well as the perivenous/periportal ratio, was reduced during starvation and in diabetes. They were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
(12 reference statements)
1
8
0
Order By: Relevance
“…Previous studies with histochemical and microchemical techniques have shown a similar zonation of the ancil lary NADPH-generating enzymes although with some controversy, probably due to con tamination from nonparenchymal cells [5]. By the same method, zonation of FAS was found to be similar to that of ACC in the female, but not in the male rat [6], Applying…”
Section: Review Of the Apparently Contradictory Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…Previous studies with histochemical and microchemical techniques have shown a similar zonation of the ancil lary NADPH-generating enzymes although with some controversy, probably due to con tamination from nonparenchymal cells [5]. By the same method, zonation of FAS was found to be similar to that of ACC in the female, but not in the male rat [6], Applying…”
Section: Review Of the Apparently Contradictory Resultssupporting
confidence: 53%
“…Most results obtained by the microanaly sis technique using microdissected samples are expressed per milligram of dry weight, as is the case in the studies by Katz et al [3,4,6], while the studies on isolated hepatocytes are usually expressed per milligram of total protein [9,10,16] or in some studies per milligram of DNA [7,16]. Contrary to this, the results of Evans et al [11,12] on the zon ation of ACC, applying digitonin-pulse per fusion [14], are expressed per milligram of cytosolic protein or as the true specific activ ity, since the assay was performed also with the isolated ACC protein.…”
Section: Expression Of Results: Choice Of Reference Substancementioning
confidence: 99%
See 1 more Smart Citation
“…Hepatic lipogenic enzymes appear to have a more perivenous distribution (32,33), whereas the rate-limiting step in bile acid synthesis, cholesterol 7␣-hydroxylase, is found mainly in periportal hepatocytes (34). Expression of hBACS was also found to have a more periportal distribution.…”
Section: Discussionmentioning
confidence: 85%
“…The techniques used in the study of hepa tocellular heterogeneity have been reviewed previously [10,23], The distribution of en-zyme activities and amounts was studied us ing histochemical [1][2][3][4], immunohistochem ical [24][25][26] and microdissective/microbiochemical techniques [26][27][28][29][30][31][32][33][34][35][36][37] as well as the digitonin dual pulse perfusion method [38], Periportal and perivenous hepatocytes were characterized functionally by using ortho-(= antera-) and retrograde liver perfusions, periportal-and perivenous-enriched hepato cyte populations [39][40][41][42][43] and periportal-like and perivenous-like hepatocytes induced in long-term primary culture [44], They were also characterized by applying noninvasive techniques with micro-light guides and with miniature oxygen electrodes positioned in periportal and perivenous areas at the liver surface for the measurement of surface fluo rescence and surface reflectance and of sur face oxygen tension, respectively [8] , 20 40 60 80 100 100 80 60 40 20 Blood level (%) Fig. 1.…”
Section: Methods For Studying Liver Cell Heterogeneitymentioning
confidence: 99%